2009
DOI: 10.3174/ajnr.a1805
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Fractional Anisotropy and Apparent Diffusion Coefficient on Diffusion Tensor Imaging in Prognosis of Neonates with Hypoxic-Ischemic Encephalopathy: A Methodologic Prospective Pilot Study

Abstract: BACKGROUND AND PURPOSE:The DTI parameters (FA and ADC) reflect the properties of the brain microstructure. Decreased anisotropy is a common feature of cerebral tissue abnormalities. Our study investigates the neurologic prognostic efficiency of these parameters in white (PLIC, CP) and gray matter (PP) in the first days of life in term neonates with HIE. We hypothesize that lesions in related brain areas could be part of a physiopathologic substratum supporting neurologic deficiencies in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…Consistent with previous reports, we found that FA values do not pseudonormalize after HIE (28), Malik et al reported a correlation between FA in the corticospinal tract and DQ at 3 mo of age, both in control infants and those who had experienced HIE, but no correlation was found in any other regions (29). Brissaud et al found that FA values in the cerebral peduncles and PLIC correlate with early neurologic function during the first week after birth (26). However, these studies used manually defined regions of interest, an approach that can potentially introduce observer error.…”
Section: Imaging Biomarkers After Hiesupporting
confidence: 80%
See 2 more Smart Citations
“…Consistent with previous reports, we found that FA values do not pseudonormalize after HIE (28), Malik et al reported a correlation between FA in the corticospinal tract and DQ at 3 mo of age, both in control infants and those who had experienced HIE, but no correlation was found in any other regions (29). Brissaud et al found that FA values in the cerebral peduncles and PLIC correlate with early neurologic function during the first week after birth (26). However, these studies used manually defined regions of interest, an approach that can potentially introduce observer error.…”
Section: Imaging Biomarkers After Hiesupporting
confidence: 80%
“…The utility of ADC measurements in HIE is limited due to pseudonormalization: typically, ADC values are lower during the first week after HIE, then return to normal, and increase further after ~2 wk; therefore postnatal age at scanning must be taken into account (18)(19)(20)(21)(22)(23). Although in several studies an ADC value of <0.78-0.85 × 10 −3 mm 2 /s in the PLIC was associated with poor outcome (22,(24)(25)(26), a recent meta-analysis of MRI biomarkers in asphyxia showed that ADC has poor specificity (64%) and sensitivity (66%) in predicting outcome (27). Consistent with previous reports, we found that FA values do not pseudonormalize after HIE (28), Malik et al reported a correlation between FA in the corticospinal tract and DQ at 3 mo of age, both in control infants and those who had experienced HIE, but no correlation was found in any other regions (29).…”
Section: Imaging Biomarkers After Hiementioning
confidence: 99%
See 1 more Smart Citation
“…24 -26 Two studies correlated these findings with neurodevelopmental outcome during the first weeks of life 25 up to months, 24 but none reported long-term outcome, including the development of UMD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the impact that FA and ADC values in this region have on outcome after ischemic injuries has been extensively described in neonates [27,28].…”
Section: Discussionmentioning
confidence: 99%